Switchable selectivity in Pd-catalyzed [3 + 2] annulations of γ-oxy-2-cycloalkenones with 3-oxoglutarates: C–C/C–C vs C–C/O–C bond formation - Liu, Yang; Oble, Julie; Poli, Giovanni (Beilstein Journal of Organic Chemistry, 2019)
Two complementary [3 + 2] annulation protocols between 3-oxoglutarates and cyclic γ-oxy-2-cycloalkenones, simply differing on the reaction temperature, are disclosed. These domino transformations allow C–C/O–C or C–C/C–C [3 + 2] annulations at will, via an intermolecular Pd-catalyzed C-allylation/intramolecular O- or C-1,4-addition sequence, respectively. In particular, exploiting the reversibility of the O-1,4-addition step, in combination with the irreversible C-1,4-addition/decarboxylation path, the intramolecular conjugate addition step could be diverted from the kinetic (O-alkylation) to the thermodynamic path (C-alkylation) thanks to a simple temperature increase. Crucial for the success of this bis-nucleophile/bis-electrophile [3 + 2] annulation is its well-defined step chronology in combination with the total chemoselectivity of the former step. This [3 + 2] C–C/O–C bond forming annulation protocol could be also extended to 1,3,5-triketones as well as 1,3-bis-sulfonylpropan-2-one bis-nucleophiles.
Keywords: 1,4-addition; annulation; decarboxylation; palladium; Pd-catalyzed allylation reaction

Handbook of Cyclization Reactions - Ma, S.-M. (Wiley-VCH, 2010)

Transition Metals for Organic Synthesis: Building Blocks and Fine Chemicals - Beller, M.; Bolm, C. (Wiley-VCH, 2004)

Handbook of Organopalladium Chemistry for Organic Synthesis - Negishi, E.-i. (Wiley-Interscience, 2002)

Palladium Reagents and Catalysts: Innovations in Organic Synthesis - Tsuji, J. (Wiley, 2004)

Palladium-Catalyzed Coupling Reactions: Practical Aspects and Future Developments - Molnár, Á. (Wiley-VCH, 2013)

Domino Reactions in Organic Synthesis - Tietze, L. F.; Brasche, G.; Gericke, K. M. (Wiley-VCH, 2006)

Domino Reactions: Concepts for Efficient Organic Synthesis - Tietze, L. F. (Wiley-VCH Verlag GmbH, 2014)

(untitled) - Tietze, L. F. (Chem. Rev., 1996)

(untitled) - Nicolaou, K. C.; Chen, J. S. (Chem. Soc. Rev., 2009)

(untitled) - Pellissier, H. (Chem. Rev., 2013)

(untitled) - Kroutil, W.; Rueping, M. (ACS Catal., 2014)

(untitled) - Larock, R. C. (J. Organomet. Chem., 1999)

(untitled) - Balme, G.; Bossharth, E.; Monteiro, N. (Eur. J. Org. Chem., 2003)

(untitled) - Zeni, G.; Larock, R. C. (Chem. Rev., 2006)

(untitled) - Majumdar, K. C.; Samanta, S.; Sinha, B. (Synthesis, 2012)

(untitled) - Poli, G.; Giambastiani, G. (J. Org. Chem., 2002)

(untitled) - Prestat, G.; Poli, G. (Chemtracts, 2004)

(untitled) - Giboulot, S.; Liron, F.; Prestat, G.; Wahl, B.; Sauthier, M.; Castanet, Y.; Mortreux, A.; Poli, G. (Chem. Commun., 2012)

(untitled) - Wahl, B.; Giboulot, S.; Mortreux, A.; Castanet, Y.; Sauthier, M.; Liron, F.; Poli, G. (Adv. Synth. Catal., 2012)

(untitled) - Kammerer-Pentier, C.; Diez Martinez, A.; Oble, J.; Prestat, G.; Merino, P.; Poli, G. (J. Organomet. Chem., 2012)

(untitled) - Lorion, M. M.; Gasperini, D.; Oble, J.; Poli, G. (Org. Lett., 2013)

(untitled) - Mao, Z.; Martini, E.; Prestat, G.; Oble, J.; Huang, P.-Q.; Poli, G. (Tetrahedron Lett., 2017)

(untitled) - Roudesly, F.; Veiros, L. F.; Oble, J.; Poli, G. (Org. Lett., 2018)

(untitled) - Pontes da Costa, A.; Nunes, D. R.; Tharaud, M.; Oble, J.; Poli, G.; Rieger, J. (ChemCatChem, 2017)

(untitled) - Borelli, T.; Brenna, S.; Broggini, G.; Oble, J.; Poli, G. (Adv. Synth. Catal., 2017)

(untitled) - Diamante, D.; Gabrieli, S.; Benincori, T.; Broggini, G.; Oble, J.; Poli, G. (Synthesis, 2016)

(untitled) - Lorion, M. M.; Duarte, F. J. S.; Calhorda, M. J.; Oble, J.; Poli, G. (Org. Lett., 2016)

(untitled) - Erray, I.; Rezgui, F.; Oble, J.; Poli, G. (Synlett, 2014)

(untitled) - Rajabi, J.; Lorion, M. M.; Ly, V. L.; Liron, F.; Oble, J.; Prestat, G.; Poli, G. (Chem. – Eur. J., 2014)

(untitled) - Lorion, M. M.; Matt, B.; Alves, S.; Proust, A.; Poli, G.; Oble, J.; Izzet, G. (Chem. – Eur. J., 2013)

(untitled) - Liu, Y.; Mao, Z.; Pradal, A.; Huang, P.-Q.; Oble, J.; Poli, G. (Org. Lett., 2018)

(untitled) - Yu, J.; Ma, H.; Yao, H.; Cheng, H.; Tong, R. (Org. Chem. Front., 2016)

(untitled) - Bonne, D.; Coquerel, Y.; Constantieux, T.; Rodriguez, J. (Tetrahedron: Asymmetry, 2010)

(untitled) - Qiu, Y.; Lan, W.-J.; Li, H.-J.; Chen, L.-P. (Molecules, 2018)
See for linear triquinane sesquiterpenoids.

(untitled) - Kutateladze, A. G.; Kuznetsov, D. M. (J. Org. Chem., 2017)
See for triquinane sesquiterpenoids.

(untitled) - Le Bideau, F.; Kousara, M.; Chen, L.; Wei, L.; Dumas, F. (Chem. Rev., 2017)
See for tricyclic sesquiterpenes.

(untitled) - Rupprecht, K. M.; Boger, J.; Hoogsteen, K.; Nachbar, R. B.; Springer, J. P. (J. Org. Chem., 1991)
See for hexahydrodibenzofurans.

(untitled) - Lutz, V.; Mannchen, F.; Krebs, M.; Park, N.; Krüger, C.; Raja, A.; Sasse, F.; Baro, A.; Laschat, S. (Bioorg. Med. Chem., 2014)

(untitled) - Fürstner, A.; Feyen, F.; Prinz, H.; Waldmann, H. (Tetrahedron, 2004)

(untitled) - Bartlett, M. J.; Turner, C. A.; Harvey, J. E. (Org. Lett., 2013)

(untitled) - Kasare, S.; Bankar, S. K.; Ramasastry, S. S. V. (Org. Lett., 2014)

(untitled) - Liu, X.; Chen, X.; Mohr, J. T. (Chem. – Eur. J., 2016)

(untitled) - Jyothi, D.; HariPrasad, S. (Synlett, 2009)

(untitled) - Hayashi, Y.; Shoji, M.; Kishida, S. (Tetrahedron Lett., 2005)

(untitled) - Allen, C. F. H.; VanAllan, J. A. (J. Am. Chem. Soc., 1950)

(untitled) - Fu, X.; Cook, J. M. (Aldrichimica Acta, 1992)

(untitled) - Winterfeldt, E.; Osterthun, V. (Chem. Ber., 1977)
With this protocol, the mechanism is expected to involve a [conjugate addition/trans-enolization/β-elimination/conjugate addition] sequence of steps.

(untitled) - Trost, B. M.; Runge, T. A.; Jungheim, L. N. (J. Am. Chem. Soc., 1980)

(untitled) - Trost, B. M.; Runge, T. A. (J. Am. Chem. Soc., 1981)

(untitled) - Giambastiani, G.; Poli, G. (J. Org. Chem., 1998)